Resin modification on interlaminar shear property of carbon fiber/epoxy/nano‐CaCO3 hybrid composites. Issue 9 (31st August 2015) - He, Hongwei; Gao, Feng
Abstract : Epoxy resin was modified by adding a silane coupling agent/nano‐calcium carbonate master batch. Then, samples of binary carbon fiber/epoxy composites and ternary fiber/nano‐CaCO3 /epoxy were prepared by hot press process. The interlaminar shear strength (ILSS) of the carbon fiber/epoxy composites was investigated and the results indicate that introduction of the treated nano‐CaCO3 enhances ILSS obviously. In particular, the addition of 4 wt% nano‐CaCO3 leads to 36.6% increase in the ILSS for the composite. The fracture surfaces of the carbon fiber/epoxy composites and the mechanical properties of epoxy resin cast are examined and both of them are employed to explain the change of ILSS. The results show that the change of ILSS is primarily due to an increase of the epoxy matrix strength and an increase of the fiber/epoxy interface. The bifurcation of propagating cracks, stress transfer, and cavitation are deduced for the reasons of strengthening and toughening effect of nano‐CaCO3 particles. POLYM. COMPOS., 38:2035–2042, 2017. © 2015 Society of Plastics Engineers